Peran Disporapar Dalam Mempromosikan Daya Tarik Wisata Kota Mojokerto Dengan Konsep Pentahelix - Ananda Sheila Umardi; Hikmah Muhaimin; Suprapto (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2025)
Each region has a tourism charm or attraction that has the opportunity to develop and expand product diversification and national tourism quality. In accordance with the Regulation of the Minister of Tourism of the Republic of Indonesia Number 14 of 2016 concerning Guidelines for Sustainable Tourism Destinations that it is important to encourage the tourism system through optimizing the roles of business (Business), government (Government), community (Community), academic (Academics), and media (Publication).This research is a qualitative research, this type of research is a case study using direct observation data collection methods. Interviews, and documentation studies, conducted at the Mojokerto City Youth Sports and Tourism Office. This study aims to find out how the Role of Disporapar is in Promoting Mojokerto City Tourism Attraction with the Pentahelix Concept. The results of the research are that the Mojokerto City Tourism Office has implemented the Pentahelix Collaboration Model in the form of Cooperation with five stakeholders, namely the government, the community (Tourism Awareness Group), the private sector , academia, and the media. The results show that there is cooperation or partnership that is carried out as a manifestation of good public governance.